Dynamics of Organizational Behavior and the Challenges of Work Stress in the Era of Modern Work Environments - Harahap, Yardina Fauziah; Ayu, Delfriana; Aidha, Zuhrina (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Background: In an era where the work environment continues to develop, work stress has become a significant challenge for employees and organizations. In an organization or company, there is a relationship between different people or consisting of several people, which is called dynamics. It is the differences between people that often lead to conflict in an organization or group, thus causing new problems related to work stress. Objective: This research aims to determine the relationship between the dynamics of organizational behavior and work stress challenges for a company. Research Method: The method used by researchers is a literature study. This article was written using the literature study method (literature review). Results: People, environment, technology, and structure are interrelated within an organization. If one of the elements above cannot be achieved in the workplace then this can affect a person's performance which will later have an impact on work stress levels. Individuals who experience work stress at work means that they do not have good group relationships in the organization, both with co-workers and their superiors. Everyone is forced to be able to face new challenges in this modern era. If we miss one step in keeping up with the times, we will have difficulty adapting to organizations that all use digital footprints.